BRAIN NATRIURETIC PEPTIDE (BNP) SEBAGAI BIOMARKER GAGAL JANTUNG KONGESTIF - Budi Darmanta Sembiring; Jekson Martiar Siahaan (Majalah Ilmiah METHODA, 2020)
Brain Natriuretic Peptide (BNP) is mainly secreted by the heart ventricles and acts as an antagonist to Renin-Angiotensin-Aldosterone. BNP is secreted as pre-proBNP which is broken down into BNP and proBNP in circulation. The BNP examination is done by measuring the levels of BNP or N-Terminal-proBNP depending on the method and the manufacturer. Increased levels of BNP and NT-proBNP indicate heart failure so that BNP and NT-proBNP are considered markers of heart failure. This examination is also indicated to help establish the diagnosis, monitoring, and prognosis of heart failure. Natriuretic peptide examination can be done by several methods such as radioimmunoassay (RIA), Enzyme immunoassay (EIA), Fluorescence immunoassay (FIA), and Sandwich Electro Chemiluminescence Immuno Assay (Sandwich ECLIA).